Implementasi Peraturan Daerah Kabupaten Bone Nomor 5 Tahun 2017 dalam Pemenuhan Rehabilitasi Vokasional bagi Penyandang Disabilitas Fisik di Kabupaten Bone - Sapri Syamsuddin; Nur Paikah; St Rahmawati; Irtiyaah Imtiyaaz Zuhri (Jurnal Hukum Lex Generalis, 2026)
This study examines the implementation of Bone Regency Regional Regulation No. 5 of 2017 on vocational rehabilitation for persons with physical disabilities in Bone Regency. Using a qualitative case study approach. The findings indicate that the policy has been implemented through skills training and assistance programs but remains constrained by limited interagency coordination, resources, service accessibility and business partnerships. Policy implementation is supported by local regulations and stakeholder commitment. Strengthened institutional synergy and expanded inclusive employment opportunities are required to enhance the independence of persons with physical disabilities.